2016
DOI: 10.1002/2015jb012636
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and geologic influences on subsidence in the vicinity of New Orleans, Louisiana

Abstract: New measurements of ongoing subsidence of land proximal to the city of New Orleans, Louisiana, and including areas around the communities of Norco and Lutcher upriver along the Mississippi are reported. The rates of vertical motion are derived from interferometric synthetic aperture radar (InSAR) applied to Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) data acquired on 16 June 2009 and 2 July 2012. The subsidence trends are similar to those reported for 2002–2004 in parts of New Orleans where ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 51 publications
2
77
0
1
Order By: Relevance
“…Muto et al [2011] observed a semicircular delta shoreline that progrades over an uneven basin floor and suggested that an existing lateral variation of basin depth does not introduce asymmetrical shoreline progradation. While subsidence rates presented here (>10 mm/yr) are extreme, they have been observed in natural systems over a time span of decades related to anthropogenic modifications [Giosan et al, 2014;Törnqvist et al, 2008;Jones et al, 2016]. Other physical experiments have shown that channels can be locked in place and become graded in a delta prograding across a shelf edge (a sudden drop of basin floor with high depth contrast), bypassing all the sediment to the deep marine environment and leaving the areas outside of the bypassing channels abandoned [Muto et al, 2016].…”
Section: Channel Mobility and Avulsion Mechanismmentioning
confidence: 67%
“…Muto et al [2011] observed a semicircular delta shoreline that progrades over an uneven basin floor and suggested that an existing lateral variation of basin depth does not introduce asymmetrical shoreline progradation. While subsidence rates presented here (>10 mm/yr) are extreme, they have been observed in natural systems over a time span of decades related to anthropogenic modifications [Giosan et al, 2014;Törnqvist et al, 2008;Jones et al, 2016]. Other physical experiments have shown that channels can be locked in place and become graded in a delta prograding across a shelf edge (a sudden drop of basin floor with high depth contrast), bypassing all the sediment to the deep marine environment and leaving the areas outside of the bypassing channels abandoned [Muto et al, 2016].…”
Section: Channel Mobility and Avulsion Mechanismmentioning
confidence: 67%
“…These results increase the probability that the extreme geodetic rates captured in Dokka et al. () represent transient phenomena, including potential growth fault movement driven by groundwater withdrawal, and are not representative of deep‐seated rates in general (Dokka, ; Jones et al., ). A more recent detailed study of the Baton Rouge‐Tepetate fault system by Shen et al.…”
Section: Introductionmentioning
confidence: 91%
“…By removing our modeled isostatic motion from the GPS records we obtain an estimate of compaction beneath the anchor depth of each receiver. Around New Orleans subsidence rates as high as 30 mm/yr or more have been measured by Jones et al (2016), largely due to local groundwater extraction. The total compaction at a GPS station must also include compaction occurring above the anchoring depth.…”
Section: 1002/2017jb014695mentioning
confidence: 99%
“…However, when the subsidence rate is modeled as a result of SIA alone, it is typically found that either the sediment loads required are very large (e.g., Ivins et al, 2007) or else the required mantle viscosity or lithosphere thickness needed to reproduce the measured uplift rates is unrealistically low (e.g., Jurkowski et al, 1984). ) Extraction of groundwater led to subsidence rates in heavily developed areas, such as New Orleans, of tens of mm/yr (Jones et al, 2016), and extraction of hydrocarbons in Southern Louisiana and Texas led to subsidence rates of tens of mm/yr, 3 orders of magnitude higher than the "background" geologic subsidence rate (Morton et al, 2006). The MD is sufficiently close to the formerly glaciated region of North America to also experience ongoing deformation as a result of GIA, which results in contemporary subsidence on the order of 1 mm/yr (Wolstencroft et al, 2014).…”
Section: Introductionmentioning
confidence: 99%